Sexual diversity and the role of educators: Reflections on a South African teacher education module - Lees, J. (South African Journal of Higher Education, 2017)
This paper is a reflection on a 5-credit, 50-hour stand-alone module titled "Sexual Diversity and the Role of Educators’" for final year pre-service education students at the Univeristy of the Western Cape in South Africa. Module development was in collaboration with 147 final year students in 2014. This paper chronicles the participatory inquiry into what pre-service educators need to be able to align their teaching practices with Section 9 of the South African Constitution. Class discussions, assignments and evaluations were used to compile this reflection. As a number of visitors to class were filmed, including Anglican Archbishop Thabo Makgoba, Cape Town’s openly gay Imam Muhsin Hendricks, young people from Cape Town’s Triangle Project and gender activist Mmapaseka Steve Letsike, students gave written permission for each aspect of their participation in the course to be shared via film and written articles. By the end of the module, students concluded that, 1) space should be provided within teacher education programmes that allow students safe and critical self-reflection on their attitudes, beliefs and norms related to sexual diversity matters; 2) that un-learning is a crucial component of learning; 3) that for many, such a personal journey requires healing spaces be created; 4) that labelling of difference used to divide people is problematic no matter what that difference may be; 5) current "LGBTI" labels should never be used to limit people’s expression of who they are; and 6) while teachers need not embrace homosexuality, teachers must defend the right of learners and colleagues to be and to practice whoever they are in the wide range of sexual differnce and otherwise.